Deep decarbonization efforts in Norway for energy sustainability. (14th June 2019) - Norby, Truls; Jensen, Emil H.; Sartori, Sabrina
ABSTRACT: Norway is self-sufficient with ample renewables while exporting large amounts of fossils fuels: It is in a unique position to fully decarbonize itself and significantly contribute to deep decarbonization globally, but the small population and economy limit the effort and impact. We discuss the efforts in Norway to reach the country's and the Paris/Katowice meetings' ambitious goals of a carbon-neutral society. Energy sustainability and the abatement of CO2 emissions have a central place in the Norwegian debate. In this perspective, we take a look at policies, strategies, and actions in Norway to realize its ambitious goals from a technological and materials development standpoint, as we are facing the change of pace after the Paris agreement in 2015 and the Katowice 2018 global climate panel meeting. Among the largest exporters of fossil fuels, Norway compensates by intensive investments in the development of carbon capture and sequestration. Following a growing debate involving the entire society, the Norwegian government has taken on aggressive strategies toward the decarbonization of energy production. We herein discuss the activities going on and the peculiar situation in Norway, which lives the rich life provided by fossil fuels while tasting the dream of being the climate knight of the world.